2014
DOI: 10.1902/jop.2013.130369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Periodontitis in the Development of Nosocomial Pneumonia: A Case Control Study

Abstract: These findings suggest that periodontal infection may influence the development of NP, highlighting that periodontitis is a factor positively associated with this respiratory tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
(142 reference statements)
1
30
0
11
Order By: Relevance
“…4 Severe asthma is characterized by the presence of daily symptoms necessitating the use of bronchodilators, incapacity, emergency hospital visits, repetitive use of systemic corticosteroids, and diminished pulmonary function. 5,7 Diseases caused by viral and bacterial infections, 7-10 as well as chronic diseases, such as periodontitis, 3,11,12 can provoke the exacerbation of bronchial inflammation, disrupted mucociliary transport, and increased mucus production, which can worsen asthma. 5,6 Several microorganisms have been related to the pathogenicity of asthma as these play an important role in respiratory disorders and can modulate the heterogeneity of this health condition.…”
mentioning
confidence: 99%
“…4 Severe asthma is characterized by the presence of daily symptoms necessitating the use of bronchodilators, incapacity, emergency hospital visits, repetitive use of systemic corticosteroids, and diminished pulmonary function. 5,7 Diseases caused by viral and bacterial infections, 7-10 as well as chronic diseases, such as periodontitis, 3,11,12 can provoke the exacerbation of bronchial inflammation, disrupted mucociliary transport, and increased mucus production, which can worsen asthma. 5,6 Several microorganisms have been related to the pathogenicity of asthma as these play an important role in respiratory disorders and can modulate the heterogeneity of this health condition.…”
mentioning
confidence: 99%
“…Conversely, other features strengthen the method, lending more quality to the study and granting it internal validity. The cutoff point established by the World Health Organization classification was used to define LBW, 20 and the criteria used for the classification of periodontal disease has good specificity and has been used in many other studies linking periodontitis to systemic conditions 23,28,34‐39 . In this context, given the current evidence on reference values ​​for gestational glycemic levels and the findings of this study that showed the overshadowing influence of maternal glycemic level in the relationship between periodontitis and LBW, mainly in mothers with an HbA1c <5.6 but also in those with an HbA1c ≥5.6 and <6.5%, it is important to highlight the need for accurate glycemic levels when studying the oral health status of females during pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…Observational studies have indicated that the presence of periodontal pathogens in dental plaque is related to the incidence of aspiration pneumonia (Terpenning et al., , ). Case–control studies have demonstrated that chronic periodontal disease, based on clinical examination, is associated with pneumonia (de Melo Neto et al., ; Gomes‐Filho et al., ). In addition, studies have shown that periodontal pathogens such as Porphyromonas gingivalis can cause lung inflammatory responses and pneumonia in an animal model (Kimizuka, Kato, Ishihara, & Okuda, ).…”
Section: Discussionmentioning
confidence: 99%